Students’ Self-Directed Learning in Digital Document Management by Using a Digital Filing Cabinet: A Case Study in Yogyakarta - Heni Setiyaningsih; Yuliansah Yuliansah (Journal of Office Administration : Education and Practice, 2025)
The learning process in archival studies has not yet reached an ideal state for achieving graduate-level competencies. The influence of ICT integration in archival practice within higher education on students’ self-directed learning remains underexplored. This study aims to analyze students’ self-directed learning in archival practice using the Digital Filing Cabinet (DFC). A descriptive quantitative approach was employed, involving 68 students enrolled in the Archival Management course at the Vocational Faculty of Yogyakarta State University. Data was collected using an online questionnaire and analyzed through descriptive statistical methods to portray students’ levels of self-directed learning. The findings reveal that the use of DFC supports the development of students’ cognitive skills and fosters self-directed learning in archival management. Further research is recommended to explore the effectiveness of DFC in relation to other variables within the archival learning process.